(untitled) (Eurasian Journal of Learning and Academic Teaching, 2025)
This article explores innovative teaching methodologies for Uzbek folk proverbs and sayings by applying an integrated approach that combines linguistics and literary studies. The study emphasizes the pedagogical value of proverbs and idiomatic expressions in developing linguistic competence, cultural awareness, and critical thinking skills among learners. It also highlights practical classroom strategies, such as contextual analysis, comparative interpretation, and creative activities, that enhance students’ ability to understand and use proverbs effectively. By merging linguistic analysis with literary interpretation, the research provides a comprehensive framework for teaching that not only improves language proficiency but also deepens appreciation of Uzbek cultural heritage.